Towards a Characterization of 'Race Law' in Medieval Wales. Issue 3 (1st September 2020) - Stevens, Matthew Frank; Phipps, Teresa
ABSTRACT: Welsh persons were subject to legal restrictions within and near Wales, from the point of local English conquest, c . 1067–1283, until the 1536 Act of Union of England and Wales. In this article we outline modern scholars' two main definitions of 'race' and 'racism' applicable to the middle ages, both 'race' as a structural relationship used to essentialize and disadvantage a group and 'race' as a package of presumed heritable physical, mental and moral traits. We then survey discriminatory laws in Wales, characterizing them as falling into four broad categories: security, economic freedom, political rights, and legal rights. The context, nature and evolution of laws within each category are discussed. We finish by testing whether this body of law amounts to 'race law' in light of the given definitions of 'race' and 'racism', concluding that it is race law by both definitions. An appendix of indicative race law is provided.